Scattering of SH waves in compact bone and cancellous bone. (May 2020) - Xiang, Meng; Qi, Hui; Qu, Zhiwei; Guo, Jing
Highlights: Firstly, it is the first time that the finite element method is used to analyze the scattering of SH wave in bone. Secondly, it is the first paper to study the scattering of SH waves in a complex closed space. Thirdly, according to the research of this paper, the degree of osteoporosis can be monitored by monitoring EFICF in bone. Fourth, this paper carried out a comparative medical test to prove electrical stimulation can promote fracture healing. Abstract: The effectiveness of electrical stimulation and Pulsed Electro Magnetic Field (PEMF) stimulation for enhancement of bone healing and osteoporosis detection has been reported by many researchers. In this paper, the scattering of SH waves by the cavity is studied analytically by using the complex variable function method. The scattering problem of electromagnetic waves by multiple cavities in bone is studied by finite element method, and the electric field intensity concentration factor around the cavity is discussed. Finally, the influence of electromagnetic wave frequency, cavity location and size on the electric field intensity concentration factor (EFICF) is analyzed, and the influence of electromagnetic wave on human skeletons is discussed. The effect of electromagnetic wave treatment on fracture healing is also illustrated by X-ray data. The theoretical reference to bone healing condition monitoring and osteoporosis detection is provided.